Cytotoxic garcimultiflorones K–Q, lavandulyl benzophenones from Garcinia multiflora branches. (August 2018) - Wang, Zhao-Quan; Li, Xing-Yu; Hu, Dong-Bao; Long, Chun-Lin
Abstract: Seven undescribed lavandulyl benzophenones garcimultiflorones K – Q, and fourteen known compounds were isolated from the CHCl3 soluble fraction of 95% EtOH extract of Garcinia multiflora branches. Their structures and absolute configurations were determined by spectroscopic techniques including NMR spectroscopy, MS analysis, and ECD calculations. Seven isolated compounds expect for garcimultiflorone L and garcimultiflorone O exhibited cytotoxic activities in vitro against five cancer cell lines (HL-60, A549, SMMC-7721, MCF-7, and SW480). It is worth mentioning that garcimultiflorone Q exhibited most significant cytotoxicities against five cancer cell lines with IC50 values ranging from 3.07–12.56 μM. Graphical abstract: Image 1 Highlights: Seven undescribed lavandulyl benzophenones were isolated from Garcinia multiflora branches. Five lavandulyl benzophenones exhibited cytotoxic activities against five cancer cell lines. Five cytotoxic compounds share some key active groups such as prenyl group and lavandulyl group.